Sintesis dan Karakterisasi Senyawa C-Vanillin Kaliks[4]Resorsinarena (CVKR) Sebagai Adsorben Zat Warna Metanil Yellow - Andriati Fitria Wati; Sri Benti Etika (Departemen Kimia FMIPA UNP, 2022)
Pollution caused by industrial waste is a problem for people's lives, one of which is water pollution by dyes. The nature of this synthetic dye is difficult to degrade, so it requires an alternative method to be able to degrade the dye. The compound C-Vaniline Kalix[4]Resorcinarene (CVKR) has great potential to be developed as an adsorbent for dye absorption. This study aims to determine the potential of C-Vanillin Kaliks [4] resorcinnarene (CVKR) as an adsorbent for the absorption of methanyl yellow dye using optimum condition parameters which are estimated to affect the methanyl yellow absorption process. The CVKR obtained was in the form of a peach colored powder solid of 0.833 grams. The results of characterization with FTIR showed absorption peaks at wave numbers 3355.12 cm-1 (OH), 1508.14 cm-1 (C=C benzene) and 1141.58 cm-1 (CO), the results of UV-Vis measurements showed the presence of absorption of conjugated dienes at a wavelength of 299 nm with an absorbance of 3.5582 A and CVKR has a melting point of 3800 C. Analysis of the absorption of methanol yellow by CVKR under optimal conditions occurred at pH 5, concentration 250 mg/L, optimum contact time 90 minutes and stirring speed 200 rpm . Adsorption tends to follow the Langmuir isotherm pattern with a determinant value of 0.9175. The precision test value (% RSD) of methanyl yellow was 1.3361%. The LOD and LOQ values in the analytical method used were 0.27568233 mg/L and 0.91894118 mg/L.